2018
DOI: 10.1088/1361-6463/aaa7d3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on spoke behaviour in HiPIMS plasma

Abstract: The objective of this paper is to study the effect of magnetic field strength on spoke behaviour in a high power impulse magnetron sputtering discharge. In three magnetic field configurations, a broad range of experimental conditions was investigated by high-speed camera imaging. The dual image feature of the employed camera enabled us to determine the shape and spoke mode number, as well as the velocity of the spokes. Five distinct spoke shapes were detected. For each magnetic field, a map was created relatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 37 publications
9
44
1
Order By: Relevance
“…This observation can be correlated to the change in the magnetic field configuration in the corners compared to the straight parts of the rectangular target. Hnilica et al have shown that increasing the magnetic field strength increases the spoke mode number [24], which is consistent with the observation of the spoke "bunching" in the curved parts of the magnetron. An increase in plasma power may cause the length of the spokes to become shorter in case of chromium or longer in case of titanium as target material.…”
Section: Spokes In Hipims Plasmas On Rectangular Magnetronssupporting
confidence: 71%
“…This observation can be correlated to the change in the magnetic field configuration in the corners compared to the straight parts of the rectangular target. Hnilica et al have shown that increasing the magnetic field strength increases the spoke mode number [24], which is consistent with the observation of the spoke "bunching" in the curved parts of the magnetron. An increase in plasma power may cause the length of the spokes to become shorter in case of chromium or longer in case of titanium as target material.…”
Section: Spokes In Hipims Plasmas On Rectangular Magnetronssupporting
confidence: 71%
“…The spoke parameters such as their shape, mode number (the number of spokes along the race track) or the propagation velocity were thoroughly determined. It has been discovered that the spoke properties are highly dependent on the discharge parameters [22][23][24], the target material [14,17,25] and the magnetic field strength [26]. In addition, the theoretical description of spokes has been presented in phenomenological models [13,14,[27][28][29][30], critical ionisation velocity models [31,32], kinetic models [33][34][35][36] or wave model [37].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the non-invasive single-shot spatial-resolved optical emission spectroscopy (OES) was conducted in nonreactive HiPIMS discharge using a titanium target in the pressure range from 0.4 to 1.6 Pa, where only the localised, well-defined spokes are present [26]. The signals of the fast photo-diode and the cylindrical Langmuir probe were utilised to capture and determine the position of a passing spoke.…”
Section: Introductionmentioning
confidence: 99%
“…The spoke has been well characterized within a number of experimental devices, including Hall thrusters [3,4,5,6,7,8,9,10,11,12,13,14,15], planar magnetrons [16,17,18,19,20,21,22,23], cylindrical magnetrons [24,25] and Penning discharges [26,27,28]. These devices feature cylindrical geometry, with electron drift and spoke propagation occurring in the azimuthal direction.…”
Section: Introductionmentioning
confidence: 99%